2019
DOI: 10.3389/fphys.2019.01256
|View full text |Cite
|
Sign up to set email alerts
|

Two Sympatric Spodoptera Species Could Mutually Recognize Sex Pheromone Components for Behavioral Isolation

Abstract: Spodoptera exigua and S. litura are two sympatric species in China and many other countries. Both moths employ a multiple component sex pheromone blend, including a common component Z9,E12-14:OAc, and two specific components Z9-14:OH and Z11-16:OAc for S. exigua, and one specific component Z9,E11-14:OAc for S. litura. For the two species, it has been well documented that males are able to recognize and behaviorally attracted by their species-specific sex pheromone, which functions as a means of reproductive is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In its native range in the Americas, the FAW share a similar geographic distribution with S. exigua [67]; thus, SfruOR13 and SfruOR16 are possibly involved in interspecific recognition between these two Spodoptera species. Very recently, we showed that sympatric S. exigua and S. litura can both perceive specific components, reinforcing behavioral isolation between the two species [68]. To analyze the correlation between PR amino acid sequence identity and the ligand specificity, we summarized the results of previous studies from these four Spodoptera species [18,19,69], and a clear correlation was shown ( Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…In its native range in the Americas, the FAW share a similar geographic distribution with S. exigua [67]; thus, SfruOR13 and SfruOR16 are possibly involved in interspecific recognition between these two Spodoptera species. Very recently, we showed that sympatric S. exigua and S. litura can both perceive specific components, reinforcing behavioral isolation between the two species [68]. To analyze the correlation between PR amino acid sequence identity and the ligand specificity, we summarized the results of previous studies from these four Spodoptera species [18,19,69], and a clear correlation was shown ( Figure 6).…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, these components are common pheromones in the genus Spodoptera . For instance, Z 9-14:OH is the minor pheromone component of Spodoptera exigua , and also serves as a behavioral antagonist against Spodoptera litura males , This suggests that one species can recognize the sex pheromone components of other sympatric species, thereby maintaining reproductive isolation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Z 9-14:OH is the minor pheromone component of Spodoptera exigua , and also serves as a behavioral antagonist against Spodoptera litura males , This suggests that one species can recognize the sex pheromone components of other sympatric species, thereby maintaining reproductive isolation. In previous studies, Spodoptera frugiperda , a species from another genus, showed similar pheromone components compared with M. loreyi , which resulted in inaccurate population monitoring of S. frugiperda in different regions. , Therefore, this ORN could detect the pheromones of sympatric species, which will be a putative target to screen the repellents of nontarget moths and improve the specificity of sex attractants when used to monitor populations of migratory pests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Females generally produce 'minor' components, which maintain speciesspecificity, and the male antennae express pheromone receptors specifically tuned to each of the pheromone components of the female blend. [7][8][9][10] These components are usually geometric isomers or analogs of the common major pheromone compound, and they share biosynthetic pathways. The species-specific minor components and the overall blend ratio are often detected by heterospecific males and cause these males to cease their pheromone-guided anemotaxis.…”
Section: Introductionmentioning
confidence: 99%